MEDIA EDUCATION AND MEDIA COMPETENCE IN MODERN SOCIO-CULTURAL CONTEXT IN TEACHING ENGLISH FOR STUDENTS OF TECHNICAL INSTITUTE (Scientific journal of the Fergana State University, 2024)
The practical goal of teaching a foreign language is to master the types of speech activity and develop the skills and abilities of oral (speaking and listening comprehension) and written (reading and writing) communication in a foreign language. The purpose of obtaining or providing information creates the need for communication. In the methodology of teaching a foreign language, exercises are divided into receptive and reproductive types.